Diseño del modelo de gestión de mantenimiento de las plantas hidroeléctricas de GPG Costa Rica - Campos-Esquivel, Kevin Mauricio (Instituto Tecnológico de Costa Rica, 2018)
lectric power generation is an area of constant growth, which not only benefits consumers, but also generates sources of employment and profits for domestic and foreign investors. Global Power Generation, a subsidiary of the Spanish company Gas Natural Fenosa, is a part of the Costa Rican energy production force. Through the management of two hydroelectric generation plants: Torito and La Joya, Global Power Generation adds a potential of 100 MW to the national electricity system. Operación y Mantenimiento Energy Costa Rica, also a subsidiary of the Spanish parent company, is in charge of the production and maintenance operations of the GPG Group. It is through O&M Energy’s work of the maintenance procedures that the need for improving the Maintenance Department was decided. This measure intends to ensure the optimal operation of the generators. The MES maintenance audit was applied to determine the degree of maturity of the Maintenance Department, that was taken as a starting point to analyze the initial situation. The result is a maintenance plan that is comprehensive, active, and in constant improvement. This guarantees the company will make the most of its available technological and human resources. As part of the implementations, a 5S program is implemented in General Warehouse area with the purpose of incorporating the Warehouse of spare parts storage together as a participative entity within the management plan. In addition, by developing Pareto analysis and developing the critical matrix within the maintenance objects of the company, the implementation of five initial stages of the management plan are achieved. This establishes the base for the continuity of the model and allows further improvement of the maintenance plans applied within the Global Power Generation's plants.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Modelo; Gestión; Mantenimiento; Auditoría; Mantenimiento Preventivo; Research Subject Categories::TECHNOLOGY::Engineering mechanics